Ketidakhati-Hatian Notaris Dalam Pembuatan Akta Berakibat Tidak Sah Akta Pernyataan Keputusan Rapat : Ketidakhati-Hatian Notaris Dalam Pembuatan Akta Berakibat Tidak Sah Akta Pernyataan Keputusan Rapat (Studi Putusan Nomor 74/Pdt/2021/Pt Btn) - Sukma, Noviantika Melati (Equality : Jurnal Hukum dan Keadilan, 2025)
Notary is one of the public officials who is authorized to make authentic deeds. Notarial Deed as an authentic deed that has perfect evidentiary power. Authentic Deed made by Notary must meet formal and material requirements, as well as the requirements for a valid agreement, if in the case of Notary does not meet one of the requirements then a notarial deed can be declared legally flawed which causes the cancellation or invalidity of the Notarial deed. The focus of this research is the consequences of the Notary's carelessness in making his legal product with a case approach to Decision Number 74 / PDT / 2021 / PT.BTN. This study concludes that LI as a Notary committed a procedural violation in making a deed by not applying the principle of caution, where the deed issued by the Notary, namely the deed of Meeting Decision Statement Number 01 dated October 5, 2015, was declared legally flawed and canceled along with its derivatives, and LI received a sanction in the form of a written warning. The purpose of this writing is to analyze and review the application of the principle of a Notary's prudence in making a Deed of Meeting Decision Statement (PKR) based on the minutes of the General Meeting of Shareholders (GMS) in the High Court Decision Number 74/PDT/2021/PT BTN. The method used is normative legal research with a case and statutory approach.